Astrophysics and Space Science Library
DOI: 10.1007/1-4020-2620-x_7
|View full text |Cite
|
Sign up to set email alerts
|

Dark Hydrogen in the Galactic Plane

Abstract: New high-resolution surveys reveal an abundance of coldf eatures in the Galactic plane. These frequently trace spiral arm structure while failing to trace CO features as well as they should if the cold ¢ ¥ £ i s primarily in molecular clouds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The same peak of emission in 12 CO and 13 CO is also observed in correspondence of Ring 3. However, in this case, as mentioned in Section 2 and Section 4.3.1, a cold HI layer is also found, as reported by Gibson et al (2004). The existence of cold (i.e.…”
Section: Ring 2-3-4: Missing Column Density and Dark Gassupporting
confidence: 82%
See 1 more Smart Citation
“…The same peak of emission in 12 CO and 13 CO is also observed in correspondence of Ring 3. However, in this case, as mentioned in Section 2 and Section 4.3.1, a cold HI layer is also found, as reported by Gibson et al (2004). The existence of cold (i.e.…”
Section: Ring 2-3-4: Missing Column Density and Dark Gassupporting
confidence: 82%
“…A cold layer of atomic hydrogen (Gibson et al 2004) has also been observed in SDPF1. As discussed in Section 6.2, this layer is seen in absorption in the HI 21cm line.…”
Section: The Content Of Sdpf1mentioning
confidence: 86%